ANTIFUNGAL ACTIVITIES OF LIPPIA EXTRACTS AND PURIFIED COMPOUNDS AGAINST PENICILLIUM DIGITATUM - Amukohe, E. S. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Postharvest decay due to a green mould known as Penicillium digitatum is responsible for significant losses in citrus exports from South Africa. Consumer concerns and stricter trade regulations have put pressure on producers to replace synthetic fungicides used commercially to prevent fungal decay with natural products. A strain was found to be resistant to the commercial fungicide Guazitine isolated from Valencia oranges. The objective of this study was to evaluate the abilities of aqueous extracts of Lippia species indigenous to South Africa (L. javanica, L.scaberrima, L.rehmannii and L. wilmsii) and isolated compounds (theviridoside, verbascoside and isoverbascoside), to inhibit the growth of this resistant strain. In vitro and in vivo tests were conducted to confirm the antifungal activity of each extract and compound. All the compounds and extracts showed significant activities in vitro against the pathogen. Although verbascoside exhibited low activity at low concentrations (0.4 mg.ml-1), its activity increased drastically at concentrations above 0.6 mg.ml-1. It was also observed that, the activities of L. rehmannii and L. javanica were the highest in vitro among the plant extracts. The in vivo results showed that L. javanica was the most potent extract at concentrations greater than 0.6 mg.ml-1. Results of the in vitro and preliminary in vivo studies suggest that employing L. javanica aqueous extracts to control P. digitatum strains resistant to Quazitin worthy of further investigation. Acknowledgements: NRF for funding